Design And Creation Of A Web-Based Customer Information System Relationship Management (Crm) Information System Based On Web On PT. Home Center Indonesia - Mirza Alfaridzi, Muhammad; Sharyanto, Sharyanto; Gunawan Sudarsono, Bernadus (Yayasan Bina Internusa Mabarindo, 2024)
PT. Home Center Indonesia is one of the companies engaged in the sale of furniture and home decor. The problem faced by the company at this time is that there is no computerized system to help manage the company's relationship with customers, so the company cannot directly contact customers quickly. In addition, customer data is still stored in Microsoft Excel which is considered less efficient, and there is no data backup which results in data at risk of being damaged or even lost. Therefore, to handle these obstacles, a web-based Customer Relationship Management (CRM) information system was created with system modeling using the Unified Modeling Language (UML) and using the PHP programming language and MySQL as a database, so that it can overcome obstacles in managing company interactions with customers and increase company competitiveness.